Analysis of the Realization of Justice in the Discretion to Terminate Prosecution - Kurniawan, Itok Dwi; Setyawan, Vincentius Patria (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Restorative justice is not just an orientation towards the goals of punishment, but has become the basic direction of criminal law enforcement in Indonesia. Settlement of criminal cases that do not have to go through formal justice process is the main jargon of restorative justice. Selecting cases that are appropriate or not to be submitted to court can be carried out by the public prosecutor with the authority to stop the prosecution. This article will analyze the discretion that the public prosecutor has to stop cases that are not suitable to be submitted to trial or through formal channels. This article was written using normative legal research methods with a conceptual approach. The results of this research are that restorative justice through discretion to terminate prosecution is a step to achieve justice in the case of public prosecutors facing cases that can be resolved using non-formal channels. Public prosecutors can facilitate alternative efforts for peace between perpetrators, victims and their families by becoming facilitators.